Febrile convulsions--what do parents do?. Issue 6148 (11th November 1978) - Rutter, N; Metcalfe, D H
Abstract : To find out about the medical and parental management of children having their first febrile convulsion a hospital-based questionnaire study was carried out in which parents were asked what they did at the time. Fifty-four out of 89 parents brought their child directly to hospital while the remainder attempted to contact their general practitioner, usually successfully, and were then referred to hospital. Whichever course of action the parents chose the outcome was satisfactory. Eighty-seven per cent of convulsions lasted for less than 15 minutes and in only two instances did they last longer than 30 minutes. One child who had convulsions for an hour was given intramuscular phenobarbitone at home without success, and the fit was finally terminated with intravenous diazepam. Parental management of the fit was often widly inappropriate. Only a few parents laid the child on his side and waited for the fit to stop. The parents were bewildered and frightened--30% thought their child was dying or dead. Education of patents of young children is needed. Simply written instructions on how to reduce the temperature of a febrile child and manage a convulsion might help.